2008
DOI: 10.1179/136404608x361828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sonoprocessing on microstructure and mechanical properties of A390 aluminium alloy

Abstract: Ultrasound is defined in terms of human hearing and it is a sound having a frequency higher than that to which the human ear can respond. The attempts to use the ultrasound at casting process have been carried out and there are a lot of study results on grain refinement on microstructure of casting alloys. However, these studies almost have been focused on mould vibration at solidifying melts of solid and liquid coexistence temperature. In this study, high intensity ultrasound was injected in aluminium full me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In the case of combining two applications the maximum value of the tensile strength is obtained. Similar results were previously reported that ultrasonic vibration caused an increase of the tensile strength of A390 [9], near-eutectic Al-Si [14], AlSi9Cu3 [19], Mg-8Li-3Al [24], AA7075 [28] alloys.…”
Section: Mechanical Propertiessupporting
confidence: 91%
“…In the case of combining two applications the maximum value of the tensile strength is obtained. Similar results were previously reported that ultrasonic vibration caused an increase of the tensile strength of A390 [9], near-eutectic Al-Si [14], AlSi9Cu3 [19], Mg-8Li-3Al [24], AA7075 [28] alloys.…”
Section: Mechanical Propertiessupporting
confidence: 91%
“…The light improvement of hardness in UST samples can be related to the finer grains induced by the treatment [ 39 ]. The smaller standard deviation in both grain size and hardness measurements can be due to the homogenizing effect of the ultrasound itself, which also promotes a more uniform microstructure and solute distribution, as already demonstrated by the authors elsewhere [ 38 , 42 ] as well as being known from literature [ 39 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 60%
“…There are numerous attempts to improve tool wear by reducing the primary silicon crystal size. Youn et al [5] and Feng et al [6] reported the use of ultrasound vibration, electromagnetic stirring was applied by Lu et al [7], while Anuradee et al [8] applied electromagnetic vibration. Beside mechanical refinements, the addition of alloying elements, such as phosphorus may refine the primary silicon as well.…”
Section: Introductionmentioning
confidence: 99%